2005
DOI: 10.1111/j.1540-8159.2005.09317.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Perfusion Assessed by 99mTc‐ECD SPECT Imaging in Pediatric Patients with Neurally Mediated Reflex Syncope

Abstract: These tilt induced regional differences in brain perfusion suggest the distinct roles of middle cerebral artery dominant territory-related vasodepressor compensation mechanisms in neurally mediated reflex syncope phenomena where cerebral lateralization of cardiac control and insular ischemia may play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Two previous studies indicated that the cerebral perfusion deficits during reflex syncope are most prominent in the frontal regions. 35,36 Accordingly, cognitive executive functions in patients with syncope due to OH were greatly affected by an orthostatic challenge. 37 However, in a separate publication on the current cohort, we found no evident effects of the identified deep WMLs on cognitive functioning.…”
Section: Resultsmentioning
confidence: 99%
“…Two previous studies indicated that the cerebral perfusion deficits during reflex syncope are most prominent in the frontal regions. 35,36 Accordingly, cognitive executive functions in patients with syncope due to OH were greatly affected by an orthostatic challenge. 37 However, in a separate publication on the current cohort, we found no evident effects of the identified deep WMLs on cognitive functioning.…”
Section: Resultsmentioning
confidence: 99%
“…The close anatomical relationship between these areas may explain the decrease in rCBF in the anterior insula and the adjacent basal and lateral temporal areas in this study. A previous SPECT study performed in pediatric patients showed that subjects with a positive tilt test had regional differences in brain perfusion, with significantly lower perfusion of the right peri-insular, posterior parietal and temporal regions compared to negative tilt test patients [17] and the reduction in rCBF in these specific areas is known to be a direct effect of the enhanced vagal reflex that leads to syncope. An rCBF decrease confined to the right insula is known to be the final trigger responsible for the reduction of heart rate and blood pressure [12].…”
Section: Discussionmentioning
confidence: 97%
“…Mean cerebral perfusion, expressed as average count densities, decreased upon provocation compared with baseline and the hypoperfusion was most pronounced in the frontal lobe. These results suggest that cerebral perfusion decreases markedly in subjects with cardiovascular vasodepressor syncope, but these studies were performed during syncopal episodes and the method with region of interest was adopted for cerebral perfusion analysis [17,34]. In the present study we used a statistical parametric mapping (SPM) technique for localizing brain regions with significant rCBF changes during the asymptomatic period in syncope patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies by using SPECT showed decreases in regional cerebral blood flow in multiple cortical regions, yielding inconsistent results across the studies. [35][36][37] The results of these SPECT studies might be interpreted as a consequence of cerebral hypoperfusion rather than a specific cause of NCS. To our knowledge, there is only 1 exploratory VBM study that showed a reduction of GM volume in the medulla in patients with NCS.…”
Section: Discussionmentioning
confidence: 99%